2017
DOI: 10.3390/brainsci7060055
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition in Adolescents with Down Syndrome: A Nonverbal Approach

Abstract: Several studies have reported that persons with Down syndrome (DS) have difficulties recognizing emotions; however, there is insufficient research to prove that a deficit of emotional knowledge exists in DS. The aim of this study was to evaluate the recognition of emotional facial expressions without making use of emotional vocabulary, given the language problems known to be associated with this syndrome. The ability to recognize six emotions was assessed in 24 adolescents with DS. Their performance was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…The results of this study were replicated in a subsequent work with the same participants: the ability to recognize basic emotional facial expressions by means of a non-verbal protocol that uses video clips rather than static photographs was adopted (Pochon and Declercq, 2014). Finally, in a recent study, Pochon et al (2017), reported new evidence on the absence of differences in emotion recognition between DS and TD matched for non-verbal ability. The authors conclude by highlighting the importance of using dynamic, strictly non-verbal tasks for participants with DS, and more generally for populations with language disorders.…”
Section: Introductionmentioning
confidence: 54%
“…The results of this study were replicated in a subsequent work with the same participants: the ability to recognize basic emotional facial expressions by means of a non-verbal protocol that uses video clips rather than static photographs was adopted (Pochon and Declercq, 2014). Finally, in a recent study, Pochon et al (2017), reported new evidence on the absence of differences in emotion recognition between DS and TD matched for non-verbal ability. The authors conclude by highlighting the importance of using dynamic, strictly non-verbal tasks for participants with DS, and more generally for populations with language disorders.…”
Section: Introductionmentioning
confidence: 54%
“…In a verbal EFER task, participants with WS could be at an advantage because of their good language skills, whereas participants with DS, who may be disadvantaged by their language problems (e.g., Grieco et al, 2015 ), perform poorly. This hypothesis is supported by the results of studies that showed no difference between the scores of participants with DS and those of TD-DA participants on a non-verbal EFER task ( Pochon and Declercq, 2013 ; Pochon et al, 2017 ).…”
Section: Introductionmentioning
confidence: 70%
“…These tasks had been examined in a study of children aged 3–11 years old to ensure that they were sensitive to advancing age and to collect typical developmental data ( Pochon et al, 2015 ). The material was the same as was used and described in detail in Pochon et al’s (2017) study.…”
Section: Methodsmentioning
confidence: 99%
“…If this scenario is indeed the case, then emotional dominance can override any other influence meaning that the resulting behavior (viewed as the person's overall expression) is marked by emotional influence. Pochon et al [45] reported only marginal differences in the recognition of different emotions. Two original experimental tasks with similar design were specifically created to examine these differences.…”
Section: Introductionmentioning
confidence: 98%